2009
DOI: 10.1007/s00268-009-9967-8
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Monitored Colonoscopic Polypectomy: Long‐Term Follow‐Up

Abstract: Long-term follow-up demonstrated that a combined endoscopic-laparoscopic approach is safe and effective. Malignant lesions identified during LMCP can be treated laparoscopically during the same operation, avoiding the need of a second procedure, with good long-term oncologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 12 publications
2
51
0
1
Order By: Relevance
“…Two patients underwent laparoscopic-assisted endoscopic polypectomy. Only two larger studies assessing this technique have been recently published (18,19). Authors concluded that this technique is safe for benign polyps and if malignancy is suspected laparoscopic colectomy can be performed without delay.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients underwent laparoscopic-assisted endoscopic polypectomy. Only two larger studies assessing this technique have been recently published (18,19). Authors concluded that this technique is safe for benign polyps and if malignancy is suspected laparoscopic colectomy can be performed without delay.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative bleeding was reported in only three studies 15,20,24 or in six patients only (0.8%). Overall postoperative complications are reported in seven of the 11 studies, 15,[18][19][20][21]23,24 ranging between 4.4-25%. Indeed, complications required surgery in only eight patients, as reported in two studies.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the global incidence of second surgical procedures is as high as 10%, which is considerable especially if compared to the 2% of patients who required further surgery after standard laparoscopic colonic resection, as reported above. 26 To be exact, in the largest studies here represented, 19 this second surgical procedure was performed under the same general anaesthesia, as the specimen was examined on frozen sections during surgery. This is a practice achieving some appreciation in the USA, but not at all common in Europe nor in Asia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 long-term colonoscopic follow up of 209 polypectomies (range: 6-196 months) showed no recurrence. 17 Mild abdominal/trocar pain was the most common complaint.…”
Section: Wood Lord Wheeler Borley Laparo-endoscopic Resection For Extmentioning
confidence: 99%